PREVALENCE AND MANAGEMENT OF POSTPARTUM URINARY RETENTION IN PREGNANT WOMEN: AN OVERVIEW (Vietnam Journal of Community Medicine, 2026)
Objectives: This narrative review aims to evaluate the prevalence, risk factors, and management outcomes of postpartum urinary retention in pregnant women.Method: A narrative review.Results: A synthesis of 8 studies indicates that the prevalence of postpartum urinary retention ranges from 10.2-24.7%. Prominent mechanical and obstetric intervention risk factors include: primiparity (accounting for an overwhelming 29.1-87.2% of cases in the affected group), instrumental delivery (31.1-35.5%), and the use of obstetric analgesia (epidural analgesia increases the risk by 3.1 times). Severe perineal trauma and a prolonged second stage of labor also significantly increase the risk of the condition. Regarding management, non-invasive conservative measures (voiding guidance, warm compresses) are the first-line and most common strategies (71.6-100%). The condition has a highly favorable recovery prognosis, with an average treatment duration of 2.0 to 4.18 days; the proportion of postpartum women regaining normal voiding ability within 48 hours is exceptionally high, ranging from 92.2-97.7%.Conclusion: Postpartum urinary retention is a common postpartum complication closely associated with primiparity, instrumental delivery, and regional anesthesia. Proactive early screening in high-risk groups and prioritizing non-invasive interventions yield high efficacy, helping the majority of postpartum women recover completely and rapidly.
Keywords: Postpartum urinary retention, risk factors, catheterization, postpartum period, obstetric analgesia.